La pandémie comme prétexte pour écrire. Sur la littérature québécoise contaminée - Berek, Ewelina (2023)
The article focuses on today’s Québécois literature and aims to show a range of practices of expression and of literary formes popular thanks to or because of the COVID-19 pandemic. During lockdown, some writers as well as amateurs, felt the urge to write. In reference to the collective "Récits infectés" (Infected stories) and Wajdi Mouawad’s lockdown diary, as well as other initiatives from the beginning of the lockdown, the article also considers the function of writing in the era of the COVID-19 pandemic.
Keywords: Québécois literature; lockdown; pandemic and literature